Chronic obstructive pulmonary disease associated with increased risk of bipolar disorder. (May 2017) - Su, Vincent Yi-Fong; Hu, Li-Yu; Yeh, Chiu-Mei; Chiang, Huey-Ling; Shen, Cheng-Che; Chou, Kun-Ta; Chen, Tzeng-Ji; Lu, Ti; Tzeng, Cheng-Hwai; Liu, Chia-Jen
Epidemiological studies have identified a trend in the development of depressive and anxiety disorders following a diagnosis of chronic obstructive pulmonary disease (COPD). However, the relationship between COPD and subsequent bipolar disorder remains unclear. From January 1, 2000, we identified adult patients with COPD from the Taiwan National Health Insurance Research Database. A nationwide population-based study was conducted; 46, 778 COPD patients and 46, 778 age-, sex-, and comorbidity-matched subjects between 2000 and 2011 were enrolled. The two cohorts were followed up till December 31, 2011 and observed for occurrence of bipolar disorder. We observed the COPD and comparison cohorts for 263, 020 and 267, 895 person-years, respectively, from 2000 to 2011. The incidence rate for bipolar disorder was 1.6/1000 person-years in the COPD cohort and 1.2/1000 person-years in the comparison cohort ( p < 0.001). After multivariate adjustment, the hazard ratio (HR) for subsequent bipolar disorder among the COPD patients was 1.42 (95% confidence interval [CI], 1.22–1.64; p < 0.001). In the COPD patients, short-acting beta-agonists (SABAs) was associated with a significantly increased risk of bipolar disorder development (HR = 1.83, 95% CI = 1.25–2.69, p = 0.002). Other COPD medications were not associated with the risk of bipolar disorder development. The study results indicate that COPD may be an independent risk factor for the development of bipolar disorder. The regular use of SABAs might increase the risk of bipolar disorder in COPD patients.